Livres et pratique de la lecture chez les chrétiens (Syrie, Liban) XVIIe - XVIIIe siècles - Bernard Heyberger (Revue des Mondes Musulmans et de la Méditerranée)
From the 17th century, the humanistic idea that man cannot attain salvation without knowing how to read penetrated Christian Arab and Greek society. This was accompanied by the circulation of the European printed works as well as by a local rebirth of the manuscript. The book became an object which was desired, sold, bought and offered. Possession of a book could mean a sign of social standing and an indication of privileged relations with "Francs".The Catholic church exercized a monopoly over the Arab printed works in the 17th century in order to control over intellectual production. Nonetheless, the circulation of manuscripts which, by definition, is less normative, permitted a certain autonomy from this intention to purge and censure. Staying within the religious domain, the arrival, in the 18th century, of the Protestant printed works, the creation of Oriental printing presses and the circulation of works originating from Orthodox regions enlarged the gamut of expression and reading material offered to Arab Christians. Local production of die printed works was, in some way, an inevitable offspring of efforts to educate the clergy and the believers.One should not simply categorize these books as religious. Rather, two principal genres may be distinguished : works of ecclesiastical science intended for the clergy and those which may be characterized as edifying literature intended for the public. This second genre deserves to be the object of more attentive study since it contributed towards shaping modern tastes and psychology of future readers living during the Arab Renaissance.